PENGARUH LAYANAN MOBILE BANKING TERHADAP KEPUASAN NASABAH PT. BANK MUAMALAT INDONESIA, Tbk KANTOR CABANG BINJAI - Mayang Julia Anggraini; Abdullah Sani; Arfan Harahap (EKSYA : Jurnal Ekonomi Syariah, 2022)
This study focuses on the discussion of the influence of mobile banking services offered by PT. Bank Muamalat Indonesia, Tbk Binjai Branch Office on customer satisfaction using the mobile banking service. The purpose of this study was to determine the effect of mobile banking services on customer satisfaction, the magnitude of the influence of mobile banking services on customer satisfaction, and the relationship between mobile banking services on customer satisfaction at PT. Bank Muamalat Indonesia, Tbk Binjai Branch Office. The type of research carried out is quantitative research that emphasizes numerical data (numbers) which is processed by inferential statistical methods (performing analysis of relationships between variables by testing hypotheses). The source of the data for this research was obtained from the answers to the questionnaire given by the research respondents, namely customers who use mobile banking services at PT. Bank Muamalat Indonesia, Tbk Binjai Branch Office. Processing and in this study using computer programs SPSS and Microsoft Office Excel. The results of the study explain that there is a significant influence between mobile banking services on customer satisfaction, this is obtained from statistical results showing a significance value of 0.000 and tcount 9.571. Based on this, it can be stated that (0.000 < 0.05) and tcount > ttable (9.571 > 1.99085) then there is an effect of variable X on Y. Mobile banking services offered by PT. Bank Muamalat Indonesia, Tbk Binjai Branch Office affects customer satisfaction by 53.4%. There is a positive or in line relationship between mobile banking services and customer satisfaction of PT. Bank Muamalat Indonesia, Tbk Binjai Branch Office.